Blockade of cannabinoid 1 receptor improves GLP-1R mediated insulin secretion in mice. (5th March 2016) - González-Mariscal, Isabel; Krzysik-Walker, Susan M.; Kim, Wook; Rouse, Michael; Egan, Josephine M.
Abstract: The cannabinoid 1 receptor (CB1) is an important regulator of energy metabolism. Reports of in vivo and in vitro studies give conflicting results regarding its role in insulin secretion, possibly due to circulatory factors, such as incretins. We hypothesized that this receptor may be a regulator of the entero-insular axis. We found that despite lower food consumption and lower body weight postprandial GLP-1 plasma concentrations were increased in CB1 −/− mice compared to CB1 +/+ mice administered a standard diet or high fat/sugar diet. Upon exogenous GLP-1 treatment, CB1 −/− mice had increased glucose-stimulated insulin secretion. In mouse insulinoma cells, cannabinoids reduced GLP-1R-mediated intracellular cAMP accumulation and subsequent insulin secretion. Importantly, such effects were also evident in human islets, and were prevented by pharmacologic blockade of CB1. Collectively, these findings suggest a novel mechanism in which endocannabinoids are negative modulators of incretin-mediated insulin secretion. Graphical abstract: Schematic representation depicting theoretical postprandial regulation of the entero-insular axis by CB1. After consuming a meal, GLP-1 is secreted into the circulation from L-cells. Upon binding to their specific receptors on pancreatic β cells, they activate adenylyl cyclase (AC), which results in increased cAMP production and PKA activation. Additionally, elevated circulating glucose concentrations lead to increased ATP production and inhibition of the ATP/K + channels, which initiates calcium (Ca 2+ ) entry through voltage-dependent Ca 2+ channels. The resultant rise of intracellular Ca 2+, in conjunction with incretin-mediated PKA activation, leads to secretion of insulin and synthesis (by NAPE-PLD and DAGL) of ECs (2-AG/AEA) (Kim et al., 2011). Subsequently, AEA/2-AG activate CB1, thereby blocking the action of incretin-mediated AC activation, which in turn negatively impacts glucose-mediated insulin secretion. (Glut2 = glucose transporter 2; PKA = protein kinase A; NAPE-PLD = N-Acyl phosphatidylethanolamine-specific phospholipase D; DAGL = Diacylglycerol lipase; 2-AG = 2-arachidonoylglycerol; AEA = anandamide. GLP-1 = glucagon-like peptide-1; GIP = glucose-dependent insulinotropic peptide). Highlights: CB1 −/− mice have improved glucose homeostasis in regular diet and high fat diet. Knocking out CB1 increases incretin secretion in mice. Cannabinoids inhibit GLP-1R-dependent insulin secretion in insulinoma cells via CB1. ACEA inhibition of insulin secretion is rescued by CB1 blockade in human islets.